CircRNA Role and circRNA-Dependent Network (ceRNET) in Asthenozoospermia - Manfrevola, Francesco; Chioccarelli, Teresa; Cobellis, Gilda; Fasano, Silvia; Ferraro, Bruno; Sellitto, Carolina; Marella, Giovanni; Pierantoni, Riccardo; Chianese, Rosanna (Frontiers in Endocrinology, 2020)
The role of circRNA in reproduction is under investigation. CircRNAs are expressed in human testis, spermatozoa (SPZ), and seminal plasma. Their involvement in embryo development has also been suggested. Asthenozoospermia, a common cause of male infertility, is characterized by reduced or absent sperm motility in fresh ejaculate. While abnormal mitochondrial function, altered sperm tail, and genomic causes have been deeply investigated, the epigenetic signature of asthenozoospermic derived SPZ still remains unexplored. CircRNAs may take part in the repertoire of differentially expressed molecules in infertile men. Considering this background, we carried out a circRNA microarray, identifying a total of 9,138 transcripts, 22% of them novel based and 83.5% with an exonic structure. Using KEGG analysis, we evaluated the circRNA contribution in pathways related to mitochondrial function and sperm motility. In order to discriminate circRNAs with a differential expression in SPZ with differential morphological parameters, we separated sperm cells by Percoll gradient and analyzed their differential circRNA payload. A bioinformatic approach was then utilized to build a circRNA/miRNA/mRNA network. With the aim to demonstrate a dynamic contribution of circRNAs to the sperm epigenetic signature, we verified their modulation as a consequence of an oral amino acid supplementation, efficacious in improving SPZ motility.